Rare germline variants in PALB2 and BRCA2 in familial and sporadic chordoma. Issue 10 (12th July 2022) - Xia, Bing; Biswas, Kajal; Foo, Tzeh K.; Gomes, Thiago T.; Riedel‐Topper, Maximilian; Southon, Eileen; Kang, Zhihua; Huo, Yanying; Reid, Susan; Stauffer, Stacey; Zhou, Weiyin; Zhu, Bin; et al.
Abstract: Chordoma is a rare bone tumor with genetic risk factors largely unknown. We conducted a whole‐exome sequencing (WES) analysis of germline DNA from 19 familial chordoma cases in five pedigrees and 137 sporadic chordoma patients and identified 17 rare germline variants in PALB2 and BRCA2, whose products play essential roles in homologous recombination (HR) and tumor suppression. One PALB2 variant showed disease cosegregation in a family with four affected people or obligate gene carrier. Chordoma cases had a significantly increased burden of rare variants in both genes when compared to population‐based controls. Four of the six PALB2 variants identified from chordoma patients modestly affected HR function and three of the 11 BRCA2 variants caused loss of function in experimental assays. These results, together with previous reports of abnormal morphology and Brachyury expression of the notochord in Palb2 knockout mouse embryos and genomic signatures associated with HR defect and HR gene mutations in advanced chordomas, suggest that germline mutations in PALB2 and BRCA2 may increase chordoma susceptibility. Our data shed light on the etiology of chordoma and support the previous finding that PARP‐1 inhibitors may be a potential therapy for some chordoma patients. Abstract : Rare germline variants in PALB2 and BRCA2 may contribute to chordoma susceptibility